Epistaxis as first manifestation of Wegener's granulomatosis. Clinical case - Casas Novas, A. (2010)
Wegener's granulomatosis is a systemic disease of unknown ethiology, characterized by a clinical triad of paranasal sinus and nasal mucosa involvement, pulmonary infiltration and cavitation, and renal disease with hematuria. Wegener's granulomatosis usually affects young or middle-aged adults. Although is uncommon in children, patients can be affected at any age.We describe a clinical case of a 14-year-old girl presentation with epistaxis, subsequent investigation showed renal failure and multiple pulmonary nodules. A positive proteinase antineutrophilic cytoplasmic antibody test supported the diagnosis of Wegener's Granulomatosis, requiring dialysis and immunosupression.